Mobile app chatbot for depressed students / Azhim Arief Ahya - Ahya, Azhim Arief (2022)
The COVID–19 epidemic has had a significant impact on many people's mental health in recent years, particularly students. During the pandemic, many students with mental disorders struggled to find solutions to cope with their depression. The project's goal is to create a simple and easy-to-use application for mentally depressed people. The mobile app features for this project are created using an artificial intelligence chatbot. Chatbots are computer programmes that communicate with people via text or voice and answer with pre-programmed responses or artificial intelligence. Future works and development include the addition of a voice chatbot function that can capture, understand, and interpret the speaker's vocal input in order to react in equivalent natural language, as well as the addition of new app features such as a depression level test and some anxiety-relieving gaming exercises.